Prescribing Pattern of Antibiotics in ENT Outpatients of Tertiary Care Hospital in Bharatpur, Nepal - Giri, Anish; Pokharel, Apar; Palikhey, Anjan; Upadhyay, Hari Prasad; Giri, Bijaya Laxmi (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Upper respiratory tract infection (URTI) like pharyngitis, tonsillitis, sinusitis, laryngitis and otitis media are the most common infections encountered in ENT outpatients. As these infections are caused by the microorganism they should be treated with the antimicrobial agents. The aim of this study was to determine the prescribing pattern of antibiotics in ENT outpatients of tertiary Care Hospital in Bharatpur, Nepal. Methods: It was prospective observational study which was carried out in the ENT Department of College of Medical Science, Bharatpur, Chitwan, Nepal. Total 267 prescriptions were studied. Patient of all age groups and sex were included in the study. Prescriptions were evaluated based on the World Health Organization (WHO) core drug prescribing indicators. Results on categorical measurements are presented in numbers and percentage which was used to generate tables and graphs. Data analysis was done by SPSS software version 20.0. Results: A total of 267 prescriptions were collected and analyzed during the study. Average number of drugs per prescription was 3.12 in which average number of antibiotic per prescription was 1.041. Commonly prescribed antibiotics belongs to the penicillin group (52%) followed by macrolide (27%). Most of the drugs were prescribed by their brand names (92%). Besides antibiotics the common adjuvant drugs that are being prescribed were nasal decongestant (44%) followed by anti-histaminics (27.7%). Conclusions: The present study highlights the wide use of Amoxicillin and clavulanic acid combination for ENT infections. Measures to emphasize the use of generic names are necessary to promote rational drug use.